2015
DOI: 10.1177/003335491513000111
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Cardiovascular Disease and Associated Risk Factors by County Type and Health Insurance Status: Results from the 2008 Ohio Family Health Survey

Abstract: Objectives. Epidemiologic studies have documented a disproportionate burden of chronic diseases in Appalachia, showing the area to be underserved by the health-care system. Nothing is known about how the health status of the Appalachian population compares with other rural or non-rural populations in the same state. We examined the associations among county type, health insurance category, and health outcomes in poorer adult Ohioans.Methods. We obtained data from the 2008 Ohio Family Health Survey, a complex l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…There have been a number of studies of this region that have shown that Appalachia is a region that has one of the highest obesity rates in the nation. 28,29 In addition, individuals living in this region are at greater risk for cardiovascular disease 30,31 , diabetes 20,21 , lung diseases 3234 , and several types of cancer 30,32,33,35 , relative to individuals in other areas. Some reasons for this may be the general lack of education in this region, low socioeconomic status, unemployment, lack of access to care, and lack of infrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a number of studies of this region that have shown that Appalachia is a region that has one of the highest obesity rates in the nation. 28,29 In addition, individuals living in this region are at greater risk for cardiovascular disease 30,31 , diabetes 20,21 , lung diseases 3234 , and several types of cancer 30,32,33,35 , relative to individuals in other areas. Some reasons for this may be the general lack of education in this region, low socioeconomic status, unemployment, lack of access to care, and lack of infrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…Such procedures, including even basic brain imaging, may not be available in many rural areas, and more advanced diagnostic procedures such as PET are typically only available in specialized academic research centers. Moreover, higher prevalence of multimorbidity in rural populations may leave rural clinicians with limited time to assess patients for emerging cognitive dysfunction using even routine bedside assessment tools.…”
mentioning
confidence: 99%
“…Although private insurance was associated with decreased mortality risk, public insurance was associated with increased mortality risk. The mechanisms have been extensively studied for how health insurance affects mortality [4,[30][31][32][33]. Previous studies have shown that socioeconomic factors, lifestyle factors, and getting care when needed played an important part in the mechanism [21,33].…”
Section: Discussionmentioning
confidence: 99%